L-Dopa Modulation of Brain Connectivity in Parkinson’s Disease Patients: A Pilot EEG-fMRI Study - Evangelisti, Stefania; Pittau, Francesca; Testa, Claudia; Rizzo, Giovanni; Gramegna, Laura Ludovica; Ferri, Lorenzo; Coito, Ana; Cortelli, Pietro; Calandra-Buonaura, Giovanna; Bisquoli, Fabio; Bianchini, Claudio; Manners, David Neil; et al. (Frontiers in Neuroscience, 2019)
Studies of functional neurosurgery and electroencephalography in Parkinson’s disease have demonstrated abnormally synchronous activity between basal ganglia and motor cortex. Functional neuroimaging studies investigated brain dysfunction during motor task or resting state and primarily have shown altered patterns of activation and connectivity for motor areas. L-dopa administration relatively normalized these functional alterations. The aim of this pilot study was to examine the effects of L-dopa administration on functional connectivity in early-stage PD, as revealed by simultaneous recording of functional magnetic resonance imaging (fMRI) and electroencephalographic (EEG) data. Six patients with diagnosis of probable PD underwent EEG-fMRI acquisitions (1.5 T MR scanner and 64-channel cap) before and immediately after the intake of L-dopa. Regions of interest in the primary motor and sensorimotor regions were used for resting state fMRI analysis. From the EEG data, weighted partial directed coherence was computed in the inverse space after the removal of gradient and cardioballistic artifacts. FMRI results showed that the intake of L-dopa increased functional connectivity within the sensorimotor network, and between motor areas and both attention and default mode networks. EEG connectivity among regions of the motor network did not change significantly, while regions of the default mode network showed a strong tendency to increase their outflow toward the rest of the brain. This pilot study provided a first insight into the potentiality of simultaneous EEG-fMRI acquisitions in PD patients, showing for both techniques the analogous direction of increased connectivity after L-dopa intake, mainly involving motor, dorsal attention and default mode networks.